Evaluation of Marginal Land Potential and Analysis of Environmental Variables of Jerusalem Artichoke in Shaanxi Province, China - Zhao, Danyun; Yin, Fang; Ashraf, Tariq; Yuan, Zheng; Ye, Linxiao (Frontiers in Environmental Science, 2022)
Based on the maximum entropy modeling (Maxent) and ArcGIS tool, this study assessed the potential of marginal land and analyzed the impact of environmental variables for Jerusalem artichoke (Helianthus tuberosus L.) in Shaanxi Province, China. The results showed that the dominant land use type for the growth of Jerusalem artichoke was moderate dense grassland. Additionally, the significant environmental variables of Jerusalem artichoke and their suitable range in Shaanxi Province were average slope (SLP, 0 - 5°), average soil depth (DPT, 1.50 - 1.60 m), max temperature of the warmest month (Bio5, 30 - 31℃), the annual mean temperature (Bio1, 16.5 - 18.0 ℃), precipitation of the wettest quarter (Bio16, 0.01 - 0.02 m), the July solar radiation (SR7, 1.66 - 1.67 × 107 W/m2), the precipitation seasonality (Bio15, 50 - 60 %), precipitation of the driest quarter (Bio17, 0 - 0.005 m) and isothermality (Bio3, 265 - 275). Furthermore, the suitable area was mainly distributed in Southern (mainly Hanzhong, Ankang and Shangluo) and Northern (mainly Yan'an and Yulin) of Shaanxi, covering around 8.81 × 1010 m2 and accounting for 42.8% of the total area of Shaanxi province. This study can provide a reference for the rational planting of Jerusalem artichoke in Shaanxi Province.